2016
DOI: 10.2105/ajph.2016.303095
|View full text |Cite
|
Sign up to set email alerts
|

Human Trafficking and Health: A Survey of Male and Female Survivors in England

Abstract: Psychological interventions to support the recovery of this highly vulnerable population are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 12 publications
4
84
1
3
Order By: Relevance
“…Failure to fulfill breadwinner expectations and feelings of guilt or shame post-trafficking is common among men [54,85]. Injuries have been also been associated with higher odds of incurring mental health disorders among labour-trafficked men [18]. Trafficked males who have incurred injuries will require both clinical services to treat physical wounds, and may also require mental health support and job placement services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to fulfill breadwinner expectations and feelings of guilt or shame post-trafficking is common among men [54,85]. Injuries have been also been associated with higher odds of incurring mental health disorders among labour-trafficked men [18]. Trafficked males who have incurred injuries will require both clinical services to treat physical wounds, and may also require mental health support and job placement services.…”
Section: Discussionmentioning
confidence: 99%
“…A study among male trafficking survivors in the UK found that 42.3% of men reported violence and 32.7% experienced injury during trafficking [18]. The limited research on trafficked men also suggests the links between acts associated with human trafficking and mental health problems, specifically indicating that injuries during trafficking, restricted freedom, physical violence, fear of traffickers and lack of a confidante were associated with symptoms of depression, anxiety and post-traumatic stress disorder [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Although not clearly established, other risk factors perhaps include diagnosis of a major mental disorder and substance use disorders. Furthermore, psychiatric disorders, including depression, anxiety, and post-traumatic stress disorders, are common sequelae of being trafficked [33,34]. Possible consequences of sex trafficking include pregnancies and sexually transmitted infections [35,36].…”
Section: Sexual Violence and Family Planningmentioning
confidence: 99%
“…Male survivors suffer the same problems in smaller numbers [17]. The loss of choice that is fundamental to trafficking leads to a loss of sense of self [18].…”
Section: Preventing Harm To Trafficking Survivor Artistsmentioning
confidence: 99%